Enhancing tea productivity through integrated fertilization and pruning management: A review - Anjarsari, Intan Ratna Dewi; Murgayanti, Murgayanti; Kadapi, Muhamad; Mubarok, Syariful; Umiyati, Uum; Nadya, Amanda; Salsabilah, Salsabilah; Azmi, Alifatul; Ramadhan, Afifah Putri; Husniah, Trifani Hana; Rosita, Rosita; Azkiya, Azkal (Kultivasi, 2026)
Tea productivity is strongly influenced by agronomic management practices, particularly fertilization and pruning, which play critical roles in regulating plant growth, physiological performance, and shoot regeneration. This review aims to synthesize current scientific evidence on how integrated fertilization and pruning management can sustainably enhance tea productivity. A narrative review approach was employed by collecting and analyzing peer-reviewed articles published between 2015 and 2025 from reputable databases, including Google Scholar and major international journals. The review highlights that balanced fertilization strategies, combining inorganic, organic, and biofertilizers, significantly improve nutrient availability, photosynthetic efficiency, and shoot yield. Pruning, when properly timed and executed, stimulates vegetative growth, maintains canopy structure, and optimizes the distribution of assimilates. Several studies demonstrated that microbial-based biofertilizers enabled a 25% reduction in inorganic fertilizer inputs without compromising tea shoot yield, while optimum pruning cycles of four to five years-maintained productivity and canopy renewal. In addition, the proportion of pecco shoots was reported to decline from approximately 70% in the first year after pruning to 19% in the fourth year, emphasizing the importance of proper pruning management.  Importantly, the integration of fertilization and pruning practices produces synergistic effects, resulting in enhanced shoot density, improved yield stability, and long-term sustainability of the plantation. This review emphasizes that integrated nutrient and canopy management is essential to address productivity decline and environmental challenges in tea plantations, providing a scientific basis for developing climate-resilient and resource-efficient tea cultivation systems.